Write better, speak better (Reader's Digest Association, 1977)
Contents: How to write better. Good writing: a skill you can learn; Secrets of good letter writing; Handling your personal correspondence; Give your letters the right look; Social notes and invitations; How to write for information; How to complain and get action; Writing your public officials; Writing to newspapers, magazines, and TV; Applying to schools and colleges; Writing and your college career; How to write a research paper; Précis, book reports, and project reports; Taking written examinations; Applying for a job...